Their little secret - Billingham, Mark (Tom Thorne novel, 2019)
"When DI Tom Thorne is called to conduct a routine assessment at the site of a suicide, he expects to be in and out in no time. But when he arrives at the metro station, where a woman named Philippa Goodwin threw herself in front of an underground train, Thorne inexplicably senses something awry and feels compelled to dig deeper. He soon discovers that she was the victim of a callous con-man who preys on vulnerable women, and whose deception plunged Philippa to her end. Thorne enlists DI Nicola Tanner to help him track down the swindler and bring him to justice. But the detective duo gets more than they bargained for when a young man's bludgeoned body turns up on the shore of a nearby seaside town. The two cases come together in a way that neither of the detectives could have foreseen"--